Chapter Le traduzioni ucraine della Divina Commedia nei secoli XX-XXI: Karmans'kyj/Ryl's'kyj, Drob'jazko, Stricha - Siedina, Giovanna (Biblioteca di Studi di Filologia Moderna, 2022)
In the present article, the author briefly retraces the stages of Dante's reception in Ukraine, then analyzes the main Ukrainian translations of Dante's Divine Comedy in the 20th-21st century, namely those by Petro Karmans'kyj, Jevhen Drob'jazko and Maksym Stricha. The author briefly dwells on Karmans'kyj's translation, highlighting the flaws already noted by H. Kočur and M. Stricha. Then the author analyzes Drob'jazko's and Stricha's translations, the only two complete Ukrainian translations of the Divine Comedy published so far. The author particularly compares the translators' approaches to potential difficulties (e.g., the rendering of verse lines or single words in Latin, the verse lines in Provencal in Purgatory, song XXVI, ll. 141-147; the translations of some characters' names, especially speaking names), and highlights the merits of their long and accurate work, which finally allowed Ukrainian readers to truly experience the Italian national poet, on one side, and filled the gap that divided Ukrainian literature from the neighboring Polish and Russian literature, on the other.